A representação social dos acadêmicos de pedagogia do IEAA-UFAM acerca da questão indígena - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Historically, the indigenous question has been linked to colonial projects that, using Christian faith and education, contributed to genocide, subordination, exclusion and discrimination of indigenous culture in all its aspects. Faced with the implemented colonialism and coloniality, negative and stereotyped representations were built about the first peoples, whichpermeates to the present day. Thus, based on this assumption, the related research carried out in the 2018- 2019 period was based on the following problematic question: The teacher training course (Pedagogy) allows academics to acquire sufficient academic and scientific knowledge on the indigenous issue, that can prepare them for the exercise of the teaching profession? To answer this concern, the following general objective was constructed: To analyze the academicscientific contribution of the Pedagogy Course at IEAA-UFAM regarding the indigenous issue and the preparation of future teachers for the exercise of the teaching profession. As a theoretical-methodological contribution, the theory of social representation was used, with a critical dialectical approach, conducting bibliographic, documentary and field research. The data collection instruments used were: the semi-structured interview and the application of the evocation test, which is part of the technique of free word association (TALP). 14 Pedagogy students from IEAA-UFAM, Humaitá-AM campus, participated in the field research, who had completed at least 80% of the course. Regarding the investigation of the indigenous issue in the Pedagogy course, the analysis of the course's PPC revealed that the current curricular project has not shown itself to be favorable to both the indigenous issue and cultural diversity. Regarding the application of the interview and evocation test, the representation of the students is based on three dimensions about the indigenous: indigenous characterization or stereotype, culture and school. It can be said that the central nucleus of the participants' representation is still linked to a stigmatized and stereotyped view of the indigenous people, however, due to the teaching and contact with indigenous culture subjects at the university, this has been changing little by little. Therefore, it is understood that, in order to contribute to the construction of a positive representation about indigenous populations, it is necessary that the PPC of the Pedagogy course undergoes a reformulation, implementing disciplines on cultural diversity as mandatory components for teacher training, which it implies a critical, post-critical and intercultural curriculum, which enables the emancipated training of teachers in relation to different cultures.
Keywords: Teoria da representação social; Pedagogia - Estudo e Ensino; Educação indígena; Formação profissional - Docentes; Formação docente - Currículo; CIÊNCIAS HUMANAS; Teoria da representação social; Formação docente; Currículo; Questão Indígena; Pedagogia